Vital Sign Prediction of Adverse Maternal Outcomes in Women with Hypovolemic Shock: The Role of Shock Index - El Ayadi, Alison M.; Nathan, Hannah L.; Seed, Paul T.; Butrick, Elizabeth A.; Hezelgrave, Natasha L.; Shennan, Andrew H.; Miller, Suellen (PLOS ONE, 2016)
Objective To determine the optimal vital sign predictor of adverse maternal outcomes in women with hypovolemic shock secondary to obstetric hemorrhage and to develop thresholds for referral/intensive monitoring and need for urgent intervention to inform a vital sign alert device for low-resource settings. Study Design We conducted secondary analyses of a dataset of pregnant/postpartum women with hypovolemic shock in low-resource settings (n = 958). Using receiver-operating curve analysis, we evaluated the predictive ability of pulse, systolic blood pressure, diastolic blood pressure, shock index, mean arterial pressure, and pulse pressure for three adverse maternal outcomes: (1) death, (2) severe maternal outcome (death or severe end organ dysfunction morbidity); and (3) a combined severe maternal and critical interventions outcome comprising death, severe end organ dysfunction morbidity, intensive care admission, blood transfusion ≥ 5 units, or emergency hysterectomy. Two threshold parameters with optimal rule-in and rule-out characteristics were selected based on sensitivities, specificities, and positive and negative predictive values. Results Shock index was consistently among the top two predictors across adverse maternal outcomes. Its discriminatory ability was significantly better than pulse and pulse pressure for maternal death (p<0.05 and p<0.01, respectively), diastolic blood pressure and pulse pressure for severe maternal outcome (p<0.01), and systolic and diastolic blood pressure, mean arterial pressure and pulse pressure for severe maternal outcome and critical interventions (p<0.01). A shock index threshold of ≥ 0.9 maintained high sensitivity (100.0) with clinical practicality, ≥ 1.4 balanced specificity (range 70.0–74.8) with negative predictive value (range 93.2–99.2), and ≥ 1.7 further improved specificity (range 80.7–90.8) without compromising negative predictive value (range 88.8–98.5). Conclusions For women with hypovolemic shock from obstetric hemorrhage, shock index was consistently a strong predictor of all adverse outcomes. In lower-level facilities in low resource settings, we recommend a shock index threshold of ≥ 0.9 indicating need for referral, ≥ 1.4 indicating urgent need for intervention in tertiary facilities and ≥ 1.7 indicating high chance of adverse outcome. The vital sign alert device incorporated values 0.9 and 1.7; however, all thresholds will be prospectively validated and clinical pathways for action appropriate to setting established prior to clinical implementation.